Marital quality from the Malay-Muslim perspective: a qualitative approach - Mohd Fadil, Fadhullah (2012)
This study aims to examine factors that may be viewed by Malaysian Muslim married individuals as constructs of marital quality. Factors related with internal-personal domain, inter-personal relationship, religiosity, gender role, and sexuality have been critically weighted in formulating the interview questions. Islamic scholars and academicians were selected for expert interviews, while in-depth face-to-face interviews with married individuals representing various marital stages were conducted to further examine the earlier findings from the expert interviews. Human ecological-life span perspective was used as guiding framework for this study. The findings implied that the concept of marital quality can be of multi-dimensions, in which, religiosity is a core domain. Indicators that were concluded include love, responsibility, harmony, satisfaction, adjustment, happiness, family management, stability, personality and appearance, relationships with family of origin, in-laws, neighbors, and friends). Most respondents agreed that satisfaction in marriage is crucial and this subjective evaluation should cover the multiple domains of married person through-out marital journey.